2019
DOI: 10.1039/c9cc01266d
|View full text |Cite
|
Sign up to set email alerts
|

Nickel phthalocyanine as an excellent hole-transport material in inverted planar perovskite solar cells

Abstract: Nickel phthalocyanine as a hole transporting material in inverted planar perovskite solar cells leads to a power conversion efficiency of 14.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Song and co-workers used thermal evaporation to introduce pristine ZnPc as an intermediate layer between the perovskite MAPbI 3 and spiro-OMeTAD. 284,285 The involvement of the ZnPc modification layer enhanced both the solar cell performance and ambient stability of PSCs. The authors further boosted the PCE of planar devices based on this ZnPc/ spiro-OMeTAD bi-HTL to 17.8% by incorporating a photon downshifting layer SrAl 2 O 4 : Eu 2+ , Dy 3+ , which improved the light-harvesting and suppressed charge recombination.…”
Section: Phthalocyanine Metal Complexes As Htl In Pscsmentioning
confidence: 99%
“…Song and co-workers used thermal evaporation to introduce pristine ZnPc as an intermediate layer between the perovskite MAPbI 3 and spiro-OMeTAD. 284,285 The involvement of the ZnPc modification layer enhanced both the solar cell performance and ambient stability of PSCs. The authors further boosted the PCE of planar devices based on this ZnPc/ spiro-OMeTAD bi-HTL to 17.8% by incorporating a photon downshifting layer SrAl 2 O 4 : Eu 2+ , Dy 3+ , which improved the light-harvesting and suppressed charge recombination.…”
Section: Phthalocyanine Metal Complexes As Htl In Pscsmentioning
confidence: 99%
“…The isomer ratio of Ni(t-Bu)4Pc with C2ν was found to be an important factor to improve external quantum efficiency [94]. In addition, recent reports showed that the use of pristine vacuum thermally deposited NiPc as hole-transport-layer in perovskite-solar cells improves the performance of the cells when compared with other metal phthalocyanines such as CuPc: values of 14.3%, 19.45 mA cm2, 1.0 V and 73.6% were obtained in the devices for maximum power conversion efficiency, short-circuit current density, open circuit voltage and fill-factor, respectively [95,96].…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…[ 20–22 ] In particular, metal phthalocyanines and their derivatives have received considerable attention for increasing the efficiency and stability of optoelectronic devices, owing to their high hole mobility, excellent thermal and chemical stabilities, and low cost. [ 20,23–25 ] Despite their advantages, unsubstituted phthalocyanines exhibit low solubility; thus, their film formation methods are limited to processes such as thermal evaporation, [ 26–29 ] or they require additional synthesis for solution processing. [ 30–33 ]…”
Section: Introductionmentioning
confidence: 99%